Предмет: Алгебра,
автор: polinaporayko
Разложите на множители выражения:
a) 27 + a³
b) 0,64a² - x²
c) 27 - (m - l)³
d) 2k² + kx - 2kx -x²
Ответы
Автор ответа:
0
27+а²=(3+а)(9-3а+а²)
0,64а²-х²=(0,8а+х)(0,8а-х)
27-(m-l)³=27-m³+m²l-3ml²+l³ или 3³-(m-l)³=(3-m+l)(9-3(m-l)+(m-l)²)=(3-m+l)(9-3m+3l+m²-2ml+l²)
2k²+kx-2kx-x²=2k(k-x)+x(k-x)=(2k+x)(k-x)
0,64а²-х²=(0,8а+х)(0,8а-х)
27-(m-l)³=27-m³+m²l-3ml²+l³ или 3³-(m-l)³=(3-m+l)(9-3(m-l)+(m-l)²)=(3-m+l)(9-3m+3l+m²-2ml+l²)
2k²+kx-2kx-x²=2k(k-x)+x(k-x)=(2k+x)(k-x)
Похожие вопросы
Предмет: Математика,
автор: ivanpetrov70
Предмет: Английский язык,
автор: viola9633
Предмет: Литература,
автор: lukyanmatviy
Предмет: Литература,
автор: katenarazumnyk
Предмет: Литература,
автор: savinychalenka